Temporary migration decisions and effects on household income and diets in rural Bangladesh - Md. Sohel Rana; Amy Faye; Matin Qaim (University of Bonn, Center for Development Research (ZEF), 2024)
Temporary migration is a widely observed phenomenon among poor rural households, mostly related to agricultural seasonality. However, household preferences for temporary migration in comparison to longer-term migration, and the differential effects of these migrations on household livelihoods are not yet well understood. Here, we use survey data collected in northern rural Bangladesh to analyze determinants of households' choice between temporary and longer-term migration, and their comparative effects on various livelihood indicators, with a particular focus on agricultural lean periods. Issues of selection bias and endogeneity are addressed with Heckman selection models and instrumental variables. We show that temporary migration is more common than longer-term migration, partly determined by family demographic and farm-labor constraints. Although longer-term migration has larger positive effects on household income, temporary migration has larger positive effects on food consumption and dietary quality during lean periods. These results suggest that temporary migration is an important mechanism for the rural poor to smooth consumption and deserves more attention by researchers and policy-makers.
Keywords: R23; J43; Q18; 330; Temporary migration; Agricultural lean periods; Food security; Nutrition; Bangladesh